Sixty Years of Academic Excellence: A Scientometric Study of Dr. Babasaheb Ambedkar Marathwada University (1963-2023) - Sarode, Anand R; Khaparde, Vaishali S.; Tayde, Suraj M (Journal of Data Science, Informetrics, and Citation Studies)
This study examines the scientific productivity of Dr. Babasaheb Ambedkar Marathwada University (BAMU) from 1963 to 2023, using the Scopus citation database. A total of 4,428 publications were analyzed using various scientometric indicators. The results show an annual growth rate of 9.92%, with 64,632 citations received, averaging 14.6 citations per paper. The Science faculty contributed the largest share of publications (95.25%), followed by multi-disciplinary fields (1.82%) and Social Sciences (1.80%). K.M. Jadhav (237 publications, 9,202 citations), M.S. Shingare (192 publications, 4,182 citations), and M.D. Shirsath (183 publications, 4,224 citations) were identified as the most prolific authors. Multi-authorship was prevalent, with a strong collaborative research culture, as evidenced by 161 institutional partnerships and international collaborations with 71 countries, notably Yemen, Saudi Arabia, and Taiwan. 8,767 unique keywords were identified, with “Time Domain Reflectometry” emerging as a key research focus. The application of Bradford’s Law of Scattering revealed that AIP Conference Proceedings is the most preferred journal in the Zone 1 category. The analysis of top-cited papers further highlights BAMU’s significant contributions to global research.
Keywords: Scientometrics; BAMU; Dr. Babasaheb Ambedkar Marathwada University; Authorship pattern; Most relevant affiliation; International collaboration.